ET ANTROPOLOGISK BLIK PÅ PSYKIATRISK SYGDOMSOPFATTELSE: Sociale og kulturelle aspekter af en sygdomsmodel for skizofreni - Johansen, Katrine Schepelern (Tidsskriftet Antropologi, 2008)
This article is about the cultural perception of schizophrenia among psychiatric staff in Denmark. The author argues that it is possible to identify a shared and coherent perception of the disease among the staff and illustrates this by introducing and discussing the theoretical concept of disease models. It is further is argued that the field of psychiatry is a pertinent environment for identifying a disease model among staff. After surveying a number of other studies, the disease model of schizophrenia is presented. It is a model where medicine and behaviour play dominant roles and where concepts of stability and chronicity are the major characteristics of the disease. Furthermore, the author presents a discussion on how the psychiatric staff seems to comprise the dominant social group in the psychiatric wards and therefore plays the major role in determining treatment